Becoming an older caregiver: A study of gender differences in family caregiving at the end of life. Issue 1 (February 2022) - Spatuzzi, Roberta; Giulietti, Maria Velia; Romito, Francesca; Reggiardo, Giorgio; Genovese, Carmela; Passarella, Michele; Raucci, Letizia; Ricciuti, Marcello; Merico, Fabiana; Rosati, Gerardo; Attademo, Luigi; Vespa, Anna
Abstract: Objectives: Older people are not traditionally expected to become caregivers. For this reason, the experience of caregiving in older persons has not been explored adequately in the research on gender differences. The objective of this study was to assess the caregiver burden among older family members who care for cancer patients facing the end of their lives, in order to compare their differences according to gender (male vs. female). Methods: This is a cross-sectional study. A total of 102 older caregivers (aged ≥65 years) of hospice patients were interviewed through the Caregiver Burden Inventory (CBI). The sample group was divided into two gender subgroups. Results: Compared with male caregivers, the older female group reported significantly higher scores in the CBI–physical subscale ( P = 0.028), and in the CBI, the overall score ( P = 0.0399) confirmed by the generalized linear model (multivariate) evaluation that included possible predictors in the model. There were no significant differences in the other CBI subscale scores (time-dependent, developmental, social, and emotional). Significance of results: Older female caregivers are at higher risk of experiencing burden and worse physical health compared with men. Further research is needed in modern palliative care to assess the role of gender differences in the experience of caregiving when the caregiver is an older person.